2020
DOI: 10.1186/s12871-020-01166-9
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid cholinergic biomarkers are associated with postoperative delirium in elderly patients undergoing Total hip/knee replacement: a prospective cohort study

Abstract: Background Postoperative delirium (POD) is a frequent complication after surgery and its occurrence is associated with poor outcomes. The neuropathology of this complication is unclear, but it is important to evaluate relevant biomarkers for postoperative status. The purpose of this study is to explore the relationship between expression levels of cholinergic biomarkers in cerebrospinal fluid (CSF) and the occurrence and development of POD in elderly patients. Methods Four hundred and ninety-two elderly pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 33 publications
6
29
0
Order By: Relevance
“…At the same time, the POD and its severity mainly diagnosed on the first and second days postoperatively by CAM and MDAS scores, which was the same as the previous study. 19 Different FiO 2 had no significant effect on the incidence of POD in 1 to 7 days postoperative between two groups. Although low FiO 2 did not impact the length of PACU and hospital stay, nor patient mortality, it indeed reduced the incidence of postoperative atelectasis.…”
Section: Discussionmentioning
confidence: 75%
“…At the same time, the POD and its severity mainly diagnosed on the first and second days postoperatively by CAM and MDAS scores, which was the same as the previous study. 19 Different FiO 2 had no significant effect on the incidence of POD in 1 to 7 days postoperative between two groups. Although low FiO 2 did not impact the length of PACU and hospital stay, nor patient mortality, it indeed reduced the incidence of postoperative atelectasis.…”
Section: Discussionmentioning
confidence: 75%
“…A recent study on postoperative delirium found that the changes in the preoperative activity of Acetylcholinesterase (AChE), Butyrylcholinesterase (BuChE) and Choline acetyltransferase (ChAT) in CSF were associated with the development of postoperative delirium in elderly patients, which may be related to central cholinergic degradation ( 108 ). Although the cholinergic deficiency hypothesis suggests treatment with acetylcholinesterase inhibitors may prevent and improve delirium two double-blind, randomized trials failed to demonstrate a statistically significant effect of cholinesterase inhibitors in the prevention and treatment of postoperative delirium ( 109 , 110 ).…”
Section: Pathophysiology and Hypothesesmentioning
confidence: 99%
“…Systemic encephalopathy/delirium is a common condition in older individuals, where tumor necrosis factor-alpha and other cytokines are thought to penetrate the blood-brain barrier. 20 In such a condition, AP can be both a cause and a result of encephalopathy/delirium.…”
Section: Ta B L E 1 Aspiration Pneumonia (Ap) In Hospital Ward Admissionmentioning
confidence: 99%